Spaces for Becomings? - Caroline King (Feminist Philosophy Quarterly, 2023)
This article examines the possibilities and limits of Paul Preciado’s book Testo yonqui (Testo Junkie) to inspire gender becomings. A genre-fluid “body-essay,” Preciado’s text follows his self-administration of testosterone in what he terms the pharmacopornographic era, a modern iteration of Foucault’s biocapitalism. After designating Preciado’s self-generated transformations as becomings, I explore how the book’s heterotopic spaces—including its genre—facilitate Preciado’s quest for a gender identity that cannot be labeled. A Foucauldian term, “heterotopia” has not yet been applied to Testo yonqui or other transgender texts, and it provides a productive template for the complex interplay of individuals and society. While I critique the vulnerability of heterotopias, and, by proxy, of Testo yonqui, to harmful power dynamics, I ultimately uphold Testo yonqui’s ability to destabilize rigid narratives of identity.